The Effect of Promotion, Product Quality, and Price on The Purchase Decision of Ventela Shoes in Malang City - Ari Wibowo; Dewi Anjaningrum, Widiya (Optima Science, 2023)
The number of local shoe brands makes the competition of local shoe manufacturers become tight, both in price competition, product quality or from other types to increase sales. So that this can be a producer task to create its own competitiveness, one of which is to promote its products as well as possible and as attractive as possible, creating quality products and can compete, and create an affordable price strategy. The purpose of this study was to determine the effect of promotion, product quality and price on Ventela shoe decisions on Ventela Shoes consumers in Malang. This research is the Explanatory Research with multiple linear regression analysis techniques. The population in this study are all Ventela Shoe consumers in Malang City whose numbers are unknown. The sampling technique used is accidental-purposive sampling with a sample of 100 respondents. The results of the multiple linear regression analysis test showed that promotion, positive and significant effect on the decision to purchase ventela shoes, and product quality also had a positive and significant effect on the decision to purchase ventela shoes. In addition, prices also have a positive and significant effect on the decision to purchase ventela shoes.